2013
DOI: 10.1016/j.ultsonch.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Enzymolysis reaction kinetics and thermodynamics of defatted wheat germ protein with ultrasonic pretreatment

Abstract: This research explores the mechanism of ultrasonic pretreatment on enzymolysis of defatted wheat germ protein (DWGP). The enzymolysis reaction kinetics and thermodynamics were studied after ultrasonic pretreatments using a probe-type sonicator and an ultrasonic cleaning bath, and the results were compared with traditional enzymolysis. The results showed that both the traditional and ultrasonic pretreated enzymolysis fit well to first-order kinetics. Both the temperature and ultrasound had a positive effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 20 publications
11
52
0
Order By: Relevance
“…It is reported that the water solubility of zein can be increased by enzymatic modification [2], and this can increase its utilization. Nevertheless, the traditional enzymolysis has many disadvantages such as low utilization rate of the enzyme, low conversion rate of the substrate, long enzymolysis time, and energy-extensive consumption [3,4]. This is largely due to the unsuitable conformation of protein, which makes it difficult for the enzyme to attack the cleavage sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the water solubility of zein can be increased by enzymatic modification [2], and this can increase its utilization. Nevertheless, the traditional enzymolysis has many disadvantages such as low utilization rate of the enzyme, low conversion rate of the substrate, long enzymolysis time, and energy-extensive consumption [3,4]. This is largely due to the unsuitable conformation of protein, which makes it difficult for the enzyme to attack the cleavage sites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the power ultrasound (20-100 kHz) is widely employed in protein enzymolysis to produce bioactive peptides [16][17][18][19], improvement of the functional properties of proteins [20][21][22][23] and synthesis of lysozyme microspheres [24]. It is reported that power ultrasound pretreatment can improve the reaction rate of enzymolysis, and the conversion rate of substrate proteins, and the bioactivity of target products significantly [4,25,26]. Moreover, ultrasound treatment can lead to changes in the secondary structure [18,27] as well as in the microstructure of protein, resulting in the exposure of more hydrolysis sites to be accessible to protease [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a related study where milk protein concentrate was treated with ultrasound at 800 W [26], an improvement in the protein hydrolysis by several proteases up to 184.9 % after pretreatment was reported, depending on the enzyme used and the pretreatment time. Likewise, an ultrasonic treatment of DWGP at 600 W and 20 °C for 10 min with the probetype sonicator and cleaning bath has shown to significantly decrease the energy barrier required for the hydrolytic reaction, improving the reaction rate [25]. SFU and fixed frequency ultrasound pretreatment at 40 ± 2 kHz have also reported to increase the degree of zein hydrolysis by approximately 11.5 % over the control, by altering the second structure of zein and rupturing the smooth surface of protein [23].…”
Section: Resultsmentioning
confidence: 99%
“…Although the potential of heat pretreatment to improve enzymatic hydrolysis of EWPs has been explored widely in the last decade [24], such method leads to destruction of some functional properties of egg white, such as gelling and foaming, which are often desirable for food manufacture [13]. Ultrasound pretreatment has also been used to improve the hydrolysis of several proteins [25] and in turn improve the production of angiotensin-converting enzyme (ACE) inhibitory peptides, by causing unfolding of protein chains and thus release possible peptides that are responsible for ACE-inhibitory activity [26]. Despite the promising effects of sonication alone or in combination with heat or pressure on a laboratory scale, there is limited information on the hydrolysis of EWPs from different ultrasound treatments and proteolytic enzyme systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation